Cardiovascular Risk and Endothelial Dysfunction: The Preferential Route for Atherosclerosis - Grassi, Davide; Desideri, Giovambattista; Ferri, Claudio (Current Pharmaceutical Biotechnology, 2011)
The vascular endothelium plays a pivotal role in the maintenance of vessel wall integrity. In this regard, endothelial cells actively regulate vascular reactivity by responding to mechanical forces and neurohormonal mediators by releasing a variety of relaxing and contracting factors. Nitric oxide (NO), an endogenous gas synthesized by NO synthases (NOSs) is the main endothelium-derived vasodilator. Continuous production of NO by constitutive NOS maintains the vasculature in a state of vasodilation, whereas its phasic generation by inducible NOS can acutely dilate an artery in response to either physiological or pathological stimuli. Under homeostatic conditions, the endothelium maintains normal vascular tone and blood flow, and there is little or no expression of proinflammatory factors. However, both traditional and novel cardiovascular risk factors initiate a chronic inflammatory process that is accompanied by a loss of vasodilator and antithrombotic factors and an increase in vasoconstrictor and prothrombotic products. Furthermore, increased oxidative stress may result in a complete derangement of the NO system, with decreased NO bioavailability and a paradoxical NOS-related oxidant generation. Because of the antiatherogenic, antithrombotic properties of NO and the proatherogenic prothrombotic actions of endogenous oxidants, a decreased NO bioavailability with increased oxidative stress will result not only in impaired endothelium-dependent vasorelaxation but also in the acceleration of atherogenesis and onset of acute atherotrombotic events. The concepts of “endothelial dysfunction” and “endothelial activation” referring to different alterations in endothelial phenotype, may contribute to the development and clinical expression of atherosclerosis.
Keywords: cardiovascular risk